PROMOTING HOTS THROUGH THINKING MAPS - Hani Rashika Mohd Salleh; Huzaina Abdul Halim, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Malaysia as a developing country is looking forward to become fully developed nation by year 2020. To achieve the Vision of 2020 as inspired by Prime Minister Tun Mahathir Mohamad, â€œInnovative Human Capitalâ€ Plan is developed with special concentration given to Higher Order Thinking Skills (hereinafter referred to as â€˜HOTSâ€™) amongst Malaysia students in school education system via thinking skill. This endeavour is taken owing to the poor performance and lack of competencies and thinking skill ability of the Malaysian students in Reading, Mathematics and Science particularly on problem solving issues which require HOTS. As a result, the Thinking Maps program has been introduced in both primary and secondary school in 2013 to stimulate the studentsâ€™ HOTS. Since then, this program has being implemented in all schools throughout Malaysia. Numerous studies have further indicate that thinking skill approach is capable to help students promote HOTS and potentials holistically provided that they are given opportunities to master English through various teaching approaches and learning activities. Despite of its promising benefits offered to, few studies reveal that majority of the students do not have ample and adequate knowledge on how to use their schema (background knowledge) while reading a text. In lieu of the above, this study is conducted to firstly explore ESL teachersâ€™ experiences on teaching students using Thinking Maps and discovers ESL teachersâ€™ teaching strategies in enhancing studentsâ€™ HOTS outcomes in reading comprehension. It also access whether the teaching of thinking skills is effectively implemented in secondary schools and examines the influence of demographic factors in promoting HOTS. The integration of Thinking Maps in the teaching-learning processes as the promotion of HOTS shall then highlight. This study employs a qualitative method in which library research has been conducted to obtain reliable data. A range of priory works namely; articles journals, International and National Policies, online database, newspapers and magazines have been reviewed and systematically analysed using content analysis approach. This study further recommends that few strategies should be implemented to enhance the application of Thinking Maps in promoting HOTS.